Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/col.22636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of density on colour and gloss variability changes of wood induced by heat treatment

Abstract: The influence of heat treatment severity (resulting from temperature) on the colour and gloss distribution changes of mahogany wood, and the effects of wood density on the responses to heat treatment were evaluated. The wood timbers with different densities were treated at 150 C to 200 C with an interval of 10 C and duration of 4 hours for heat treatment schedules. The colour parameters (lightness L * , red-green axis value a * , yellow-blue axis value b * ) and gloss (parallel and perpendicular to the grain) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown that heattreated wood of different colors can be obtained by adjusting the temperature and time of heat treatment [8,9], and the gloss value of the wood after heat treatment is low. Due to the heat treatment, the uniformity of the color and gloss of the exposed surface of the wood improves [10], so as to realize the diversification of product varieties. Most studies have shown that the color change in heat-treated wood is highly dependent on the wood species [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that heattreated wood of different colors can be obtained by adjusting the temperature and time of heat treatment [8,9], and the gloss value of the wood after heat treatment is low. Due to the heat treatment, the uniformity of the color and gloss of the exposed surface of the wood improves [10], so as to realize the diversification of product varieties. Most studies have shown that the color change in heat-treated wood is highly dependent on the wood species [11].…”
Section: Introductionmentioning
confidence: 99%